Manifestation of regional government commitment to the implementation of local batik painting policy - Andarwanto, Nanang; Birsyada, Muhammad Iqbal; Nasution, Nasution (Harmoni Sosial: Jurnal Pendidikan IPS, 2022)
This research aims to discover the commitment and obstacles of the Bantul Regency Government, Yogyakarta Special Region, in recognizing, facilitating, fostering, and protecting education units and education programs based on local excellence. The research approach was used qualitatively. The technique of determining the research subject was purposive. The research data were collected through observation, in-depth interviews, and documentation. The data were analyzed using inductive techniques: data reduction, presentation, and verification. The results showed that the commitment was realized by forming a P2D (Basic Education Developer) team based on local wisdom and children's rights. P2D conducts local content education development programs in batik through workshops, mapping, coaching, training, seminars, socialization, festivals, competitions, monitoring, and evaluation. The obstacles experienced by the Bantul district government in implementing the local content education policy lie in the need for more human resources (batik teachers) and the lack of time allocated for learning.